Legal Procedure and Formalities of Marriage Application in the State of Selangor: A Way Forward - Nik Salida Suhaila Nik Saleh; Kamarul Adrian Akmar Noor Azmi; Nur Jihan Mardhiah Mohd. Nawi; Nur Yasmin Zawani Pakror Rozi; Siti Nurfaqihah Syafiqah Mustafa Kamal; Amar Haziq Abd Shukur (An-Nisa: Journal of Islamic Family Law, 2025)
This paper considers the legal procedure and formalities of marriage application in the State of Selangor. While the Islamic Family Law (State of Selangor) Enactment 2003 has provided detail provisions on the marital related matters, it still needs clearer provisions and amendments on the security of marriage institution. The objective of this paper is to study whether the marriage requirements stated in the Enactment have upheld positive values and whether the marriage procedures have complicated the process of application. This is important to answer the issues of marriage syndicate which has created holistic challenges in Malaysia. The authors employed quantitative methods in searching for the answers by analysing the Enactment in understanding the legal procedures and formalities stated therein. This paper also proposed that amendment of the law is necessary to prevent issues related to procedure and formalities of marriage in the State of Selangor. The authors have found that the procedures and formalities upheld positive values and do not complicate the process. Family lineage can be well taken care of if things that are prohibited in marriage can be prevented legally.